Address of Frances E. Willard, President of the Woman's National Council of the United States (founded in 1888), at its first triennial meeting, Albaugh's Opera House, Washington, D.C., February 22-25, 1891. - Willard, Frances E. (Frances Elizabeth), 1839-1898.; National Council of Women of the United States; Catt, Carrie Chapman, 1859-1947; National American Woman Suffrage Association Collection (Library of Congress); YA Pamphlet Collection (Library of Congress) (Washington, D.C. : R.H. Darby, printer, 1891)
The National Council of Women of the United States was created in 1888 at the recommendation of Elizabeth Cady Stanton to further the goal of women's rights. It includes interesting information on the ideological differences between Willard and Stanton, as well as a discussion of "Scientific Motherhood," and the worldwide WCTU.
Cover title.
Also available in digital form on the Library of Congress Web site.
Keywords: Women's rights -- United States; Women and religion